The future of small farms for poverty reduction and growth - Hazell, Peter B. R.; Poulton, Colin; Wiggins, Steve; Dorward, Andrew R. (International Food Policy Research Institute, 2007)
The people operating small farms in developing countries have to cope with the risks of these small businesses and have long faced heavy challenges. Today, these challenges are particularly severe, and the aspirations of young people on small farms have changed. Globalization and the integration of international markets are stimulating intense competition, offering some opportunities but also new risks. In light of these pressures and others, many of the world’s millions of small farmers are simply not making it. Indeed, half of the world’s undernourished people, three-quarters of Africa’s malnourished children, and the majority of people living in absolute poverty live on small farms. The transformation of the small-farm economy is one of the biggest economic challenges of our time. For some, it entails growth into specialized, market-oriented farms; for others, part-time farming combined with off-farm rural jobs; and for others, a move out of agriculture. The pathways of transformation differ by region and location and will take decades. Policy must take a long-run view to support and guide this process efficiently, effectively, and in social fairness. The role of women farmers and their livelihoods requires particular attention. In this paper, Peter Hazell, Colin Poulton, Steve Wiggins, and Andrew Dorward address several crucial questions. Do small farms in fact have a future? In what situations can small farms succeed? What strategies are most appropriate for helping to raise small-farm productivity? The authors review both sides of the debate over the future of small farms before coming to their conclusions. Coming down firmly on the side of policy support for small farms, they point to small farms’ significant potential for reducing poverty and inequity. They also clarify the differing roles of and needs for small farms in different country contexts and spell out a policy agenda for promoting small-farm development. This discussion paper is based on a literature review and the deliberations of an international workshop, “The Future of Small Farms,” organized by the International Food Policy Research Institute (IFPRI) 2020 Vision Initiative, the Overseas Development Institute (ODI), and Imperial College London in Wye, England, from June 26 to 29, 2005. (A proceedings volume for this workshop is available from IFPRI, www.ifpri.org/events/seminars/2005/smallfarms/sfproc.asp.) We hope that this discussion paper will help stimulate renewed attention among many stakeholders— including policymakers, researchers, the private sector, and nongovernmental organizations—to small-scale agricultural development. Healthy and productive small farms could serve as a crucial mechanism for achieving the poverty and hunger Millennium Development Goals.